PERILAKU IBU DALAM MEMILIH DUKUN BAYI SEBAGAI PENOLONG PERSALINAN PADA KOMUNITAS SUKU TALANG MAMAK TAHUN 2022 - Dona Martilova; Susani Hayati (JOMIS (Journal of Midwifery Science), 2023)
Indragiri Hulu Regency has indigenous people, namely the Talang Mamak Tribe Community. The largest community of the Talang Mamak tribe is in Rakit Kulim District. Based on the data, it was found that in 2018 there were 2 cases, in 2019 there were 2 cases, in 2020 there was 1 case, and in 2021 there was 1 case. Of all the cases of maternal death, the history of delivery assistance was assisted by a traditional birth attendant. This study aims to explore the behavior of mothers in choosing a traditional birth attendant in the Talang Mamak tribe community in 2022. This research is qualitative with a phenomenological approach. Methods of data collection through indepth interviews using interview guidelines.The selection of informants was carried out purposefully. The informants in this study consisted of 5 main informants who gave birth with criteria for a history of childbirth assisted by a traditional birth attendant in the last 6 months, as well as 3 supporting informants: a health center midwife and village staff. The results of the study show that the behavior of mothers seeking childbirth assistance is related to knowledge, customs and traditions, beliefs, distance, and economy. It is suggested to the public health centre to carry out outreach and training on the partnership of traditional birth attendants again so that midwives and traditional birth attendants can become partners so that delivery assistance with health workers can be achieved.